A CORPUS LINGUISTICS INVESTIGATION OF TWO NEAR-SYNONYMOUS WORDS: RICH AND WEALTHY - Nugroho, Dwi Yulianto (Universitas Nusantara PGRI Kediri, 2018)
Many language learners, even language teachers, consider two words are synonymous. In fact, some words are not really synonymous. This sometimes triggers questions among language learners. They are confused whether two considered-synonymous words can be used interchangebly in certain contexts. Their confusion will appear more when they should describe something. Therefore, this study tries to find out phenomena around two words which are considered synonymous, namely rich and wealthy. Using British National Corpus (BNC) as the data which were analysed using the software Sketch Engine (SkE), this corpus linguistics based study found out that rich and wealthy are near-synonyms because they have identical sense but they are not substitutable for certain contexts. In addition, rich is more commonly used by people to describe both human and non-human beings. The results of the study imply that corpus linguistics provide benefits for English language teaching as we can really analyse language using authentic facts compiled in a corpus. A language teacher can also use corpus linguistics to teach vocabulary. In addition, a sociolinguistics phenomenon found out in this study implies that investigating two considered-synonymous adjectives can help language learners understand how people use the adjectives in socialising with other people. Keywords: Corpus Linguistics, near synonyms, British National Corpus, Sketch Engine